Clifford the big red dog. Clifford's big Halloween - Lions Gate Home Entertainment (Santa Monica, CA : Lions Gate Home Entertainment, 2006)
Goofy ghosts, spooky costumes, and leaf piles are all part of the fun when Clifford and his pals share in the fall festivities on Birdwell Island.
Boo -- Leaf of absence -- A new dog in town -- Not now, I'm busy -- Clifford's carnival -- Come back, Mac -- Dino Clifford -- The trouble with kittens.
Title from container.
Special features: Speckle stories; Trailer gallery; "Carve your own pumpkin" game.
Suitable for ages 2 and up.
DVD, region 1; Dolby Digital 2.0 stereo., digitally mastered.
English or dubbed Spanish dialogue; closed-captioned for the hearing impaired.
Keywords: Clifford (Fictitious character : Bridwell) -- Juvenile drama; Halloween -- Juvenile drama; Video recordings for the hearing impaired; Animated television programs; Television programs for children; Adventure television programs; Fantasy television programs